Digital technology innovation promotes green transformation: Empirical evidence from Chinese manufacturing enterprises - Zihan Song; Manli Jia; Youwei Ma (Sustainable Futures)
Digital technology innovation (DTI) has become increasingly important for promoting green transformation (GT) in the manufacturing sector. Based on the panel data of manufacturing enterprises listed on the Shanghai and Shenzhen A-share markets from 2011 to 2023, this work investigates the DTI’s impact on GT and the underlying mechanism. Our results show that, first, every unit increase in DTI results in the increase of the degree of GT by an average of 39.0 %; Second, DTI facilitates the GT primarily through improving the quality of environmental information disclosure (EIDQ); Third, pressures from environmental regulation(EPRP) and social public opinion(SPOP) further enhance the promotion of DTI on GT; Last, invention-based DTI has a more pronounced effect on promoting GT than utility model-based DTI, and DTI is more effective in facilitating substantive GT than strategic GT. Overall, the knowledge thus gained may serve as valuable insights for promoting GT on a global scale, particularly in the developing countries.